CENTRAL VERTIGO - Sela Pricilia; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2021)
Central vertigo is a symptom characterized by a feeling of changes in body position or environment as a result of diseases originating from the central nervous system. Central vertigo is caused by a disease that extend from vestibular nuclei in medulla oblongata to ocular motor nuclei and integration system in mesencephalon to vestibulocerebellum, thalamus and vestibular cortex in temporoparietal and the neuronal pathway which mediate VOR (vestibulo-ocular reflex). The diseases can be vestibular migrain, TIA (Transient Ischemic Attack), Vertebrobasilar ischemic stroke, multiple sclerosis, tumor in cerebelopontine angle and congenital malformation like Dandy Walker Syndrome. Central vertigo can be diagnosed by performing several special tests. This examination can also distinguish central vertigo from its differential diagnosis, namely peripheral vertigo. Management of central vertigo can be in the form of acute attack management and specific management according to the cause.